Predictive thermodynamics for ionic solids and liquids. Issue 31 (14th June 2016) - Glasser, Leslie; Jenkins, H. Donald Brooke
Abstract : Thermodynamic properties of ionic solids and liquids may reliably be predicted using volume-based thermodynamics (VBT) and thermodynamic difference rules (TDR). Abstract : The application of thermodynamics is simple, even if the theory may appear intimidating. We describe tools, developed over recent years, which make it easy to estimate often elusive thermodynamic parameter values, generally (but not exclusively) for ionic materials, both solid and liquid, as well as for their solid hydrates and solvates. The tools are termed volume-based thermodynamics (VBT) and thermodynamic difference rules (TDR), supplemented by the simple salt approximation (SSA) and single-ion values for volume, V m, heat capacity, , entropy, , formation enthalpy, Δf H °, and Gibbs formation energy, Δf G °. These tools can be applied to provide values of thermodynamic and thermomechanical properties such as standard enthalpy of formation, Δf H °, standard entropy, , heat capacity, C p, Gibbs function of formation, Δf G °, lattice potential energy, U POT, isothermal expansion coefficient, α, and isothermal compressibility, β, and used to suggest the thermodynamic feasibility of reactions among condensed ionic phases. Because many of these methods yield results largely independent of crystal structure, they have been successfully extended to the important and developing class of ionic liquids as well as to new and hypothesised materials. Finally, these predictive methods are illustrated by application to K2 SnCl6, for which known experimental results are available for comparison. A selection of applications of VBT and TDR is presented which have enabled input, usually in the form of thermodynamics, to be brought to bear on a range of topical problems. Perhaps the most significant advantage of VBT and TDR methods is their inherent simplicity in that they do not require a high level of computational expertise nor expensive high-performance computation tools – a spreadsheet will usually suffice – yet the techniques are extremely powerful and accessible to non-experts. The connection between formula unit volume, V m, and standard thermodynamic parameters represents a major advance exploited by these techniques.